A novel function of geranylgeraniol in regulating testosterone production. Issue 6 (3rd June 2018) - Ho, Hsin-Jung; Shirakawa, Hitoshi; Giriwono, Puspo E; Ito, Asagi; Komai, Michio
Abstract: Isoprenoids play widely differing roles in various physiological processes in animals and plants. Geranylgeraniol (GGOH) is an isoprenoid found in plants, and is an important metabolic derivative in the isoprenoid/cholesterol synthesis pathway. Earlier studies focused on GGOH's ability to improve the side effects of bisphosphonate therapy by regulating the mevalonate pathway. More recently, the mevalonate pathway-independent effects of GGOH have been described, including anti-inflammatory, anti-tumorigenic, and neuroprotective activities. It is noteworthy that GGOH regulates the steroidogenesis pathway in testis-derived I-10 tumor cells. Testosterone is a hormone produced via steroidogenesis in testicles and plays a role in fetal development and the male reproductive system. GGOH enhanced testosterone and progesterone (its precursor) levels in I-10 cells by activating adenylate cyclase via cAMP/PKA signaling, without altering phosphodiesterase activity. These findings highlight the potential benefits of GGOH as a therapeutic agent for low testosterone levels, such as late-onset hypogonadism in men. Abstract: : Geranylgeraniol enhances testosterone production.